2016
DOI: 10.1371/journal.pone.0158061
|View full text |Cite
|
Sign up to set email alerts
|

Survival Predictors for Severe ARDS Patients Treated with Extracorporeal Membrane Oxygenation: A Retrospective Study in China

Abstract: Extracorporeal membrane oxygenation (ECMO) is increasingly being applied as life support for acute respiratory distress syndrome (ARDS) patients. However, the outcomes of this procedure have not yet been characterized in severe ARDS patients. The aim of this study was to evaluate the outcomes of severe ARDS patients supported with ECMO and to identify potential predictors of mortality in these patients. A total of 38 severe ARDS patients (aged 51.39±13.27 years, 32 males) who were treated with ECMO in the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
2
12
1
Order By: Relevance
“…ECMO has been our preferred method of support since March 2012, and most patients were transplanted on intraoperative venoarterial ECMO. The ECMO implantation technique, circuits, and cannula types used at our institution have been reported elsewhere [13]. We used centrifugal pumps (Bioline, Maquet, Hirrlingen, Germany) at a flow rate of 3-5 L/min in all patients.…”
Section: Ecmo Managementmentioning
confidence: 99%
“…ECMO has been our preferred method of support since March 2012, and most patients were transplanted on intraoperative venoarterial ECMO. The ECMO implantation technique, circuits, and cannula types used at our institution have been reported elsewhere [13]. We used centrifugal pumps (Bioline, Maquet, Hirrlingen, Germany) at a flow rate of 3-5 L/min in all patients.…”
Section: Ecmo Managementmentioning
confidence: 99%
“…For instance, chronic immunosuppression was associated with increased mortality both in Enger et al’s [54] score (OR 2.6, 95% CI 1.3–5.2) and the VV-ECMO [56] mortality score (OR 2.9, 95% CI 1.1–7.9). Liu et al [55] found an underlying lung disease (i.e. COPD, interstitial lung disease and lung cancer) to be an independent risk factor for mortality (OR 12.2, 95% CI 1.2–122.2; p  = 0.033).…”
Section: Survival Prediction Modelsmentioning
confidence: 99%
“…The use of prone position was not reported in this data collection, despite the recently documented beneficial of this intervention . Similarly, other scores included variables which were either quite uncommon (such as a preexisting lung disease in the score by Liu et al . or difficult to assess in these patients (such as the pre‐ECMO neurological status assessed by the Glasgow Coma Scale included in the score by Cheng et al.…”
Section: Discussionmentioning
confidence: 99%
“…The seven risk scores published so far were all derived from patients already on ECMO support, thus being appropriate for predicting survival in these patients and not for selecting which patients should or should not be submitted to ECMO. The PRESERVE (PRedicting dEath for Severe ARDS on VV‐ECMO) study was published in 2013 and was constructed with eight pre‐ECMO parameters .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation